Impact of Different Location of Incisions on Surgically Induced Astigmatism (SIA) after Phacoemulsification: A Comparative Study (Medical Forum Monthly, 2021)
Objective: To evaluate the Impact of different locations of incisions on surgically induced astigmatism (SIA) after phacoemulsification.Study Design: Longitudinal studyPlace and Duration of Study: This study was conducted at the Khairpur Medical College and Teaching Hospital, Khairpur Mir’s from July 2020 to December 2020.Materials and Methods: A longitudinal study in which 100 patients with Keratometric Astigmatism of 1.5 D or less were included in the study after their consent. The participants were divided into two groups based on the type of incision. Group A received a Limbal incision, whereas, in Group B, a clear corneal incision was carried out. The pre and post-operative Keratometry K1 and K2 readings were recorded and tabulated on a data sheet. Data were analyzed using SPSS Version 21.0 and the paired t-test was applied to compare the mean K1 and K2 values of the different types of incisions at different sites (Superotemporal and Superonasal).Results: Significant differences were seen in the K1 and K2 (P=0.002, P=0.039) Superotemporal readings in Group A. No significant difference was seen in the K1 and K2 (P=0.339, P=0.337) Superonasal readings in Group A. Significant difference was seen in the K1 and K2 (P≤0.001, P≤0.001) Superotemporal readings in Group B. Significant difference was seen in the K1 and K2 (P≤0.001, P≤0.001) Superonasal readings in Group B.Conclusion: Both successfully showed less SIA post-operatively, however, Limbal incision induced less SIA after cataract surgery.